One silence, different clinical pictures - Magalhães, Patricia (2022)
Landau Kleffner syndrome (LKS) is a rare epileptic encephalopathy characterized by acquired receptive and expressive aphasia and epileptic seizures in a previously normal child. The diagnosis can be challenging and commonly mistaken with other clinical pictures, namely emotional conditions, mainly when identifiable triggers are present in the patient’s history. The authors present the case of a four-year-old Portuguese girl who moved to China with her parents and sister and started presenting regression of expressive and comprehensive language and behavioral problems around the same time that they changed country. The aim of this study is to document a case of LKS and briefly review the subject, highlighting the complexity of the differential diagnosis.